Posisi Bahasa Jawa Jembersebagai Alat Komunikasi pada Masyarakat Banyumasan: Tinjauan Bourdieu di Desa Jatimulyo Kecamatan Jenggawah Kabupaten Jember - Sulihtyaningrum, Eli; Eddyono, Aryo Subarkah (ppjbsip, 2024)
This research investigates the phenomenon of language competition between Megelen (a dialect of Javanese spoken in Banyumas) and Jemberan (a dialect of Javanese spoken in Jember) within the context of communication among multi-ethnic communities in the village of Jatimulyo. The aim is to understand the dominance of Jemberan Javanese and the reasons behind its usage in communication among the Banyumas community. A qualitative approach is adopted, employing Bourdieu's framework of social practice logic (agent-habitus-mode-field), with observations conducted in family settings, neighborhoods, and public spaces. Data is gathered through triangulation of sources including observations, interviews, and document reviews. Data analysis follows Miles and Huberman's qualitative analysis method (reduction, presentation, and drawing conclusions/verification). The findings indicate that Jemberan Javanese dominates as a communication tool due to its symbolic power, although Banyumas Javanese dialects are maintained as distinctions within family and neighborhood contexts. These findings support the view that Bourdieu's framework of social practice logic is dynamic and relevant for analyzing cultural phenomena such as shifts in language use. AbstrakPenelitian ini membahas fenomena persaingan bahasa antara bahasa Megelen (bahasa Jawa dialek Banyumasan) dan bahasa Jawa dialek Jember dalam konteks komunikasi masyarakat multi-etnis di desa Jatimulyo. Tujuannya adalah untuk memahami dominasi penggunaan bahasa Jawa dialek Jember dan alasan di baliknya dalam komunikasi masyarakat Banyumasan. Pendekatan kualitatif digunakan dengan mengadopsi kerangka logika praktik sosial Bourdieu (agen-habitus-moda-ranah), di mana observasi dilakukan pada ranah keluarga, rukun tetangga, dan ruang publik. Data diperoleh melalui triangulasi sumber yang melibatkan hasil observasi, wawancara, dan penelusuran dokumen. Analisis data menggunakan metode analisis kualitatif Miles dan Huberman (reduksi, penyajian, dan penarikan kesimpulan/verifikasi). Hasil penelitian menunjukkan bahwa bahasa Jawa dialek Jember mendominasi sebagai alat komunikasi karena kekuatan simbolik yang dimilikinya, meskipun bahasa Jawa dialek Banyumasan tetap dipertahankan sebagai distingsi dalam ranah keluarga dan tetangga. Temuan ini mendukung pandangan bahwa kerangka logika praktik sosial Bourdieu dapat dinamis dan relevan untuk menganalisis fenomena budaya seperti perubahan dalam penggunaan bahasa.